Analysing the Use of Hedging in Medical Academic Writing - Hashim, Sattar (Thi Qar Arts Journal, 2024)
The current study aims to identify, categorize, and specify the functions of the hedges found in the study corpus. The study corpus consists of 50 research articles (RAs) in diverse medical disciplines written in English at Turkish universities. The study adopts the taxonomy proposed by Hyland (1994) to identify and analyze the hedges found. The found hedges are counted manually. The findings showed how important to use hedges in medical research articles. Also, the findings showed the necessity of being knowledgeable and aware of the vital roles and functions that hedges play in academic writing in general, and medical research articles writing in particular. The study presented several implications for future researchers and authors.